Features of judicial reform in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The Constitution of the Republic of Kazakhstan declares that everyone has the right to protection of the rights andfreedoms through the courts. Judicial authority is exercised on behalf of the Republic of Kazakhstan. Under theConstitution, the court of justice by the courts alone. The main task of this Court to protect the rights, freedoms andlegitimate interests of citizens and legal entities, enforcement provisions of the Constitution, constitutional laws andother regulations, as well as international treaties. On November 20 of this past year, the VI Congress of the Republicof Kazakhstan Judge main focus was on the performance of the judge and the judicial system in 4 years.Keywords: court, judicial authority, judge, judicial reform, congress judge, mediation.